Deinococcus fonticola sp. nov., isolated from a radioactive thermal spring in Hungary. Issue 6 (30th April 2019) - Makk, Judit; Enyedi, Nóra Tünde; Tóth, Erika; Anda, Dóra; Szabó, Attila; Felföldi, Tamás; Schumann, Peter; Mádl-Szőnyi, Judit; Borsodi, Andrea K.
Abstract : A Gram-stain-negative, aerobic, non-motile and coccus-shaped bacterium, designated strain FeSDHB5-19 T, was isolated from a biofilm sample collected from a radioactive thermal spring (Budapest, Hungary), after exposure to 5 kGy gamma radiation. A polyphasic approach was used to study the taxonomic properties of strain FeSDHB5-19 T, which had highest 16S rRNA gene sequence similarity to Deinococcus antarcticus G3-6-20 T (96.5 %). The 16S rRNA gene sequence similarity to type strains of other Deinococcus species were 93.0 % or lower. The DNA G+C content of the draft genome sequence, consisting of 3.9 Mb, was 63.9 mol%. Strain FeSHDB5-19 T was found to grow at temperatures of 10–32 °C (optimum, 28 °C) and pH 5–10 (pH 6.5–7.5) and tolerated up to 1.5 % NaCl (w/v) with optimum growth at 0–0.5 % NaCl. The predominant fatty acids (>10 %) were C16 : 0 and C16 : 1 ω7 c . The cell-wall peptidoglycan type was A3β l -Orn–Gly1-2 . The whole-cell sugars were glucose and low amounts of galactose. Strain FeSDHB5-19 T possessed MK-8 as the predominant respiratory quinone, typical of the genus Deinococcus . The polar lipid profile contained unidentified phosphoglycolipids and unidentified glycolipids. The isolate was found to be highly resistant to gamma (D10 <8 kGy) and UV (D10 800 J m −2 ) radiation. According to its genotypic, phenotypic and chemotaxonomic characteristics, strain FeSDHB5-19 T represents a novel species in the genus Deinococcus, for which the name Deinococcus fonticola sp. nov. is proposed. The type strain is FeSDHB5-19 T (=NCAIM B.02639 T =DSM 106917 T ).